Differential DNA methylation of the meiosis‐specific gene FKBP6 in testes of yak and cattle–yak hybrids. (22nd September 2016) - Li, B; Luo, H; Weng, Q; Wang, S; Pan, Z; Xie, Z; Wu, W; Liu, H; Li, Q
Contents: FK506‐binding protein 6 (FKBP6) is essential for meiosis during mammalian spermatogenesis. However, the molecular regulation of FKBP6 during spermatogenesis remains unclear. In the present study, we performed molecular characterization of the meiosis‐specific gene FKBP6 in yak testes. Yak FKBP6 encodes a polypeptide of 295 amino acid residues with an FK506‐binding domain (FKBP_C) and three tetratricopeptide repeat domains. The methylation level of the FKBP6 promoter in testes was significantly higher in cattle–yak with male sterility than in yak, and the FKBP6 promoter was methylated in liver tissues in which FKBP6 is not expressed. FKBP6 promoter activity was significantly decreased after treatment with the M.SssI methyltransferase in vitro . Furthermore, the FKBP6 gene was remarkably activated in bovine mammary epithelial cells treated with the DNA methyltransferase inhibitor 5‐aza‐2‐deoxycytidine. Taken together, our results demonstrate for the first time that the FKBP6 promoter is differentially methylated in testes; together with the functional promoter analysis, this suggests that methylation of this promoter may contribute to cattle–yak male infertility.